'100 metres to the liquor store and 300 meters to the cemetery' – individual, social, environmental and organisational facilitators and barriers to thriving in Swedish sheltered housing models. Issue 5 (18th May 2023) - Corneliusson, Laura; Sköldunger, Anders; Sjögren, Karin; Edvardsson, David
Abstract: In Sweden, sheltered housing is a housing model that provides accessible apartments with elevated social possibilities for older people. The environment within sheltered housing is expected to support resident health and reduce the need for care services. A previous study has shown that with increasing levels of depressive mood and decreasing levels of self-rated health and functional status, those residing in sheltered housing report higher levels of thriving compared to those ageing in place. Therefore, the aim of this study was to illuminate aspects of sheltered housing that are facilitators and/or barriers to thriving. Seven semi-structured group interviews in five different sheltered housing accommodations in Sweden were conducted between April 2019 and January 2020 (N = 38). The results, analysed using qualitative content analysis and presented in a model developed by Grol and Wensing, illuminate the four main categories of facilitators and barriers to thriving: individual factors, social context, environmental factors and organisational context. The results of this study show that the factors that influence experiences of thriving in sheltered housing are multifaceted and interconnected. Although the supportive environment provided in sheltered housing seems to contribute to thriving, the limited consideration towards the shifting health of residents is a barrier to thriving. The results of this study may assist in implementing tailored interventions to help support thriving on various levels.